دور الأطر الاجتماعية في تشكيل المضامين المعرفية المدرسية - مناصرية, ميمونة; بدوي, أم الخير (Sciences humaines; Vol. 33 (2014): SCIENCES HUMAINES)
يعرف  "سوسيولوجيا المنهاج"  بأنه الرؤية أو المنظور الفكري الموجه لدراسة ما تحتويه المضامين المدرسية في علاقتها بالأطر الاجتماعية ، الأمر الذي منح هذا المجال أهمية بالغة ضمن ميادين المعرفة التربوية والمدرسية خاصة .  ويأتي هذا الموضوع ليميط اللثام عن  سوسيولوجيا المنهاج من خلال جملة من الاتجاهات الفكرية التي حاولت التعرف على ماهيته ودوره في المعرفة السوسيولوجية وكذا تطوره عبر التاريخ الذي منحه موقعا هاما ضمن ميادين العلم والمعرفة .   « sociology of curriculum» is Known  to be a vision or  an intellectual perspective directed to study  what school contexts contain and their relationship with the school social frameworks, which give this area  an extreme importance within the fields of educational knowledge and  especially school ones. this subject  comes to unveil the sociology of the curriculum through  a set of intellectual trends that have tried to identify what it is and its role in the sociological knowledge  as well as its development through history  which gives it  an important position within the fields of science and knowledge.